Resurgence and critical youth empowerment in Whitefish River First Nation. Issue 4 (1st October 2016) - Kope, Jared; Arellano, Alexandra
ABSTRACT: Sport/play-based programs are part of new proposed solutions to provide educational and structured opportunities to empower youth and foster social change and community mobilization. While answering a recent call for more research examining these socio-political processes within sport-for-development programs, the purpose of this paper is to explore how the Indigenous youth experiences of the Youth Leadership Program (YLP) from the organization Right To Play could support what Indigenous scholars have called resurgence. This self-conscious traditionalism movement calls for Indigenous critical self-reflection, political thought, and cultural revival that are at the heart of re-empowerment and self-determination. Youth experiences enacted through the YLP are documented through the Critical Youth Empowerment (CYE) model that highlights processes of critical reflection leading to socio-political change. While providing a general appreciation of the YLP program and the application of the CYE model within an Indigenous context, the findings suggest that, to serve resurgence, culture and local knowledge need to be central in empowerment processes and youth programming.